The rehabilitation of tropical soils using compost and vermicompost is affected by the presence of endogeic earthworms - Jouquet, Pascal; Plumere, Thierry; Doan Thu, T.; Rumpel, C. (Elsevier, 2010)
As soil engineers, earthworms play a key role in soil organic matter turnover and ecosystem functioning. Numerous studies have shown their positive influence on plant growth and soil quality. At the same time, organic matter inputs in compost or vermicompost, produced in the presence of earthworms, are valuable soil amendments that may increase plant growth. However, whether the combination of earthworm activity and organic matter amendments can be a successful approach for soil rehabilitation remains insufficiently studied. The aim of the present study was to determine the interactions between Dichogaster bolaui , an endogeic earthworm species, and compost or vermicompost produced by Eisenia andrei , an epigeic earthworm species, in a degraded tropical soil. We assessed nutrient availability and natural vegetation recovery. Treatments with and without D. bolaui earthworms were compared. The incorporation of both types of organic matter improved soil quality (i.e., higher pH, more C and nutrients) and led to the recovery of vegetation growth (i.e., development of seedlings and higher above- and belowground biomass). Mineral nutrients, on the other hand, had no effect on vegetation development and led to more pollution of groundwater (i.e., higher concentrations of N-NH 4 +, N-NO 3 - , K and P). Although we could not draw definite conclusions about whether vermicompost had a more positive effect on plant growth than compost, this substrate improved soil chemical properties compared with compost. Dichogaster bolaui enhanced leaching of N-NH 4 + , N-NO 3 - and K when mineral nutrients were used. However overall, D. bolaui had a neutral impact on plant growth when combined with compost, but a negative effect when in combination with vermicompost inputs. In conclusion, this experiment demonstrated that organic matter amendment is an interesting alternative for the rehabilitation of tropical soils. However, negative interactions can occur between local endogeic earthworms and vermicompost.